Anti-Inflammatory Effects of Pineapple Core Extract on Macrophages in Gingivitis-Induced Wistar Rats - Niswatun Chasanah; Sawitri Dwi Indah Pertami; Dzanuar Rahmawan; Risyandi Anwar; Gabrilia Dwi Agustina (Universitas Muhammadiyah Semarang, 2026)
Background: Gingivitis is the earliest stage of periodontal disease, characterized by gingival inflammation, edema, and bleeding. This condition involves infiltration of inflammatory cells, including macrophages, which play a regulatory role through pathogen phagocytosis and pro- inflammatory cytokine secretion. Pineapple core (Ananas comosus L. Merr) contains several bioactive constituents—such as bromelain, flavonoids, and tannins—that have been reported in the literature to exhibit anti-inflammatory and antioxidant properties. Bromelain, a proteolytic enzyme abundantly present in pineapple core according to previous studies, is known to modulate inflammatory pathways through cytokine suppression.Objective: This study aimed to evaluate the effect of pineapple core extract on macrophage cell counts in gingivitis-induced Wistar rats.Method: A post-test only design was used with 30 male rats allocated into three groups: control (CMC-Na), 12.5% extract, and 25% extract. Gingivitis was induced, followed by three days of treatment. Gingival tissues were processed histologically, and macrophage-like cells were quantified under light microscopy.Outcome: The mean macrophage counts were 27.38 (control), 13.60 (12.5%), and 7.66 (25%), with significant differences among groups (p < 0.05).Conclusion: These findings indicate that pineapple core extract can reduce macrophage infiltration in gingival tissues, and the higher concentration demonstrates a stronger anti-inflammatory effect.